Method for detecting grafting rate of grafting material for photovoltaic adhesive film
By digging the photovoltaic adhesive film into a film material with grafting material and using the peak area ratio of infrared characteristic peaks for detection, the problem of inaccurate detection of internal grafting in the prior art is solved, and the grafting rate test is improved accuracy.
Patent Information
- Application Number
- CN202411609600.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-21
AI Technical Summary
In the prior art, the graft rate detection method of the grafting material for photovoltaic films cannot accurately detect the grafting situation inside the particles, and the test is inaccurate due to uneven grafting.
By dividing the graft material into a film material, and using the peak area ratio of infrared characteristic peaks for detection, combined with lamination equipment and ethanol soaking, the graft rate is accurately detected.
The accuracy of the graft rate test of the graft material for photovoltaic films can be improved, and the graft rate can be detected more accurately, which enhances the reliability of the test data.
Smart Images

Figure CN119492704A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of grafting rate detection, and in particular, relates to a method for detecting the grafting rate of a grafting material for a photovoltaic adhesive film. Background Art
[0002] Photovoltaic films include photovoltaic POE films and photovoltaic EVA films. Photovoltaic POE films use POE resin as the main raw material, while photovoltaic EVA films use EVA resin as the main raw material.
[0003] In the prior art, the grafting rate of the grafting material for photovoltaic film is detected by using an infrared spectrometer to quantitatively detect the content of the additive, and also by using infrared spectroscopy to detect the particles extruded by the reaction. The specific detection process is as follows:
[0004] First, soak the particles of the grafted material in acetone for 2 hours. After soaking, dry them in an oven for 6 hours. Then use infrared spectroscopy to detect the peak area ratio of the infrared spectrum. Then, use the prepared standard curve (by adding a certain amount of additives to correspond to the peak area ratio on the infrared spectrum) to obtain the added additive grafting rate. However, when using an infrared spectrometer to detect the particles of the grafted material, only the reflection method can be used to measure the infrared spectrum of a single particle. This detection method can only detect the grafting of additives on the surface of the particles, but not the grafting inside the particles. At the same time, if it is due to mixing materials or grafting equipment, it may cause uneven grafting of particles. This will also lead to inaccurate testing of the grafting rate, and the reliability of the test data is questionable.
[0005] It is hoped to provide an improved method for detecting the grafting rate of a grafting material for photovoltaic adhesive films, particularly with regard to how to improve the accuracy of the grafting rate test. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a method for detecting the grafting rate of a grafting material for photovoltaic adhesive film, the purpose of which is to improve the accuracy of the grafting rate test of the grafting material for photovoltaic adhesive film.
[0007] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a method for detecting the grafting rate of a grafting material for photovoltaic film, comprising the steps of:
[0008] S1, after the grafted material is mixed evenly, sampling is performed;
[0009] S2, refining the grafted material into a film material on an open mill;
[0010] S3, taking a film material of a set size as a first film sample, and making the first film sample into a second film sample with a flat surface;
[0011] S4, placing the second film sample in the solution for soaking;
[0012] S5, drying the second film sample;
[0013] S6, testing the infrared spectrum of the second film sample, and calculating the peak area ratio of the second film sample;
[0014] S7, preparing a standard curve of the relationship between the additive content in the particles and the infrared peak area ratio;
[0015] S8. Calculate the grafting rate of the grafted material.
[0016] In the step S2, the thickness of the film material is 0.09-0.11 mm.
[0017] In the step S3, the first film sample is melted into the second film sample by a laminating device.
[0018] In the step S3, the temperature when laminating the first film sample is 65-75°C.
[0019] In step S4, the solution is ethanol.
[0020] In the step S4, the second film sample is placed in the solution for immersion for at least 3 hours.
[0021] In the step S4, the second film sample is placed in the solution for soaking at least once.
[0022] In the step S5, the temperature for drying the second film sample is 35-45° C., and the drying time is at least 2 hours.
[0023] In the step S6, the peak area ratio A1 of the second film sample is calculated according to the obtained target characteristic peak absorbance peak area S1 and the characteristic peak absorbance peak area S2 of the particle itself, where A1=S1 / S2.
[0024] The step S7 comprises:
[0025] S701, sampling particles that have not been grafted and contain additive components;
[0026] S702, refining the particles into a film material on a refining mill;
[0027] S703, taking a film material of a set size as a third film sample, and manufacturing the third film sample into a fourth film sample with a smooth surface;
[0028] S704, testing the infrared spectrum of the fourth film sample, and calculating the peak area ratio of the fourth film sample;
[0029] S705, repeating steps S701 to S704 to obtain peak area ratio data of particles with different additive contents;
[0030] S706. Prepare a standard curve.
[0031] The grafting rate detection method of the grafting material for photovoltaic adhesive film of the present invention solves the problem of uneven grafting material by means of open refining film forming, and at the same time, the peak area ratio of the infrared characteristic peak can be used to accurately detect the grafting rate, thereby improving the accuracy of the grafting rate test of the grafting material for photovoltaic adhesive film. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] This specification includes the following drawings, which show the following contents:
[0033] Figure 1 It is a flow chart of the method for detecting the grafting rate of the grafting material for photovoltaic adhesive film of the present invention;
[0034] Figure 2 It is an infrared spectrum;
[0035] Figure 3 It is a standard curve graph; Figure 4 This is a flowchart of step S7. DETAILED DESCRIPTION
[0036] The specific implementation methods of the present invention are further explained in detail below by describing the embodiments with reference to the accompanying drawings, with the aim of helping those skilled in the art to have a more complete, accurate and in-depth understanding of the concept and technical solution of the present invention and facilitating its implementation.
[0037] like Figure 1 As shown, the present invention provides a method for detecting the grafting rate of a grafting material for photovoltaic film, comprising the steps of:
[0038] S1, after the grafted material is mixed evenly, sampling is performed;
[0039] S2, refining the grafted material into a film material on an open mill;
[0040] S3, taking a film material of a set size as a first film sample, and making the first film sample into a second film sample with a flat surface;
[0041] S4, placing the second film sample in the solution for soaking;
[0042] S5, drying the second film sample;
[0043] S6, testing the infrared spectrum of the second film sample, and calculating the peak area ratio of the second film sample;
[0044] S7, preparing a standard curve of the relationship between the additive content in the particles and the infrared peak area ratio;
[0045] S8. Calculate the grafting rate of the grafted material.
[0046] Specifically, in the above step S1, the prepared grafting material is stirred to mix the particles uniformly, and random sampling is performed 3 times, with a small amount of sampling (about 30 grams, and the appropriate amount can be determined according to the size of the actual mixing mill used).
[0047] In the above step S2, 30 g of the grafted material is mixed evenly on an open mill to form a film material.
[0048] Preferably, the thickness of the membrane material is 0.09-0.11 mm. Exemplarily, the thickness of the membrane material is 0.1 mm (the grafted material uses POE or EVA particles as a substrate. When detected by infrared transmission method, the membrane sample should be as thin as possible. In actual use, samples with a thickness of about 0.1 mm can be well detected in infrared spectra).
[0049] There are wrinkles on the surface of the first film sample. In the above step S3, the first film sample is melted into a second film sample with a smooth surface by a laminating device to avoid affecting the infrared detection and ensure the accuracy of the detection.
[0050] In the above step S3, a small piece of the first film sample is taken for lamination. The temperature of the first film sample during lamination is 65-75°C. For example, the temperature can be 70°C, 71°C or 72°C. The first film sample melts under the set temperature to form a layer of the second film sample with a dense and smooth surface. The second film sample should not have holes and wrinkles to avoid affecting infrared detection. The temperature of 65-75°C is just the melting point of the particles, and the additive will not react.
[0051] In the above step S4, the solution is ethanol, and the second film sample is placed in the solution for soaking for at least 3 hours. The second film sample is soaked in ethanol for 3 hours, and the soaking time can be extended if necessary to soak out the additives that are not grafted in the sample (solvents such as xylene cannot be used to avoid dissolving the particle molecules and the grafted particle molecules).
[0052] In the above step S4, the second film sample is placed in the solution for soaking at least once. The soaking times of the second film sample can be once, twice or three times, etc., and the soaking time of each soaking is at least 3 hours, which can fully discharge the auxiliary agent that is not grafted in the second film sample, which helps to improve the accuracy of the test results.
[0053] In the above step S5, the temperature when drying the second film sample is 35-45°C, illustratively, the temperature can be 36°C, 38°C or 40°C, and the drying time is at least 2 hours. The drying temperature should be selected according to the soaking solvent and the particle substrate used, and the film material should not be melted while drying the soaking solvent.
[0054] In the above step S6, after the dried second film sample is cut into a suitable size, the second film sample is tested for infrared spectrum on the transmitted infrared to obtain the target characteristic peak absorbance peak area S1 and the characteristic peak absorbance peak area S2 of the particle itself, and then the peak area ratio A1 of the second film sample is calculated based on the obtained target characteristic peak absorbance peak area S1 and the characteristic peak absorbance peak area S2 of the particle itself, A1=S1 / S2.
[0055] like Figure 4 As shown, the above step S7 includes:
[0056] S701, sampling particles that have not been grafted and contain additive components;
[0057] S702, refining the particles into a film material on a refining mill;
[0058] S703, taking a film material of a set size as a third film sample, and manufacturing the third film sample into a fourth film sample with a smooth surface;
[0059] S704, testing the infrared spectrum of the fourth film sample, and calculating the peak area ratio of the fourth film sample;
[0060] S705, repeating steps S701 to S704 to obtain peak area ratio data of particles with different additive contents;
[0061] S706. Prepare a standard curve.
[0062] In the above step S7, the ungrafted additive-containing particles mainly refer to particles containing various additive components that have not undergone the grafting reaction step. In the above step S701, the prepared particles are stirred to mix the particles evenly, and random sampling is performed 3 times, with a small amount of sampling (about 30 grams, which can be determined according to the size of the actual mixing mill).
[0063] In the above step S702, 30 g of particles are mixed evenly on an open mill to form a film material.
[0064] Preferably, the thickness of the film material is 0.09-0.11 mm, and illustratively, the thickness of the film material is 0.1 mm.
[0065] There are wrinkles on the surface of the third film sample. In the above step S703, the third film sample is melted into a fourth film sample with a smooth surface by a laminating device to avoid affecting the infrared detection and ensure the accuracy of the detection.
[0066] In the above step S703, a small piece of the third film sample is taken for lamination. The temperature of laminating the third film sample is 65-75°C. For example, the temperature can be 70°C, 71°C or 72°C. The third film sample is melted under the set temperature to form a fourth film sample with a dense and smooth surface. The fourth film sample cannot have holes and wrinkles to avoid affecting infrared detection. The temperature of 65-75°C is just the melting point of the particles, and the additive will not react.
[0067] In the above step S704, after the fourth film sample is cut into a suitable size, the fourth film sample is tested for infrared spectrum in the transmitted infrared to obtain the target characteristic peak absorbance peak area S3 and the characteristic peak absorbance peak area S4 of the particle itself, and then the peak area ratio A2 of the fourth film sample is calculated based on the obtained target characteristic peak absorbance peak area S3 and the characteristic peak absorbance peak area S4 of the particle itself, A2=S3 / S4.
[0068] In the above step S7, each time step S701 to step S704 is performed, the additive content in the particles is different. For example, when step S701 to step S704 is re-performed for the first time, the additive content in the particles is 0.5%, and the peak area ratio A2 of the fourth film sample is calculated; when step S701 to step S704 is performed for the second time, the additive content in the particles is 1.0%, and the peak area ratio A2 of the fourth film sample is calculated; when step S701 to step S704 is performed for the third time, the additive content in the particles is 2.0%, and the peak area ratio A2 of the fourth film sample is calculated; when step S701 to step S704 is performed for the fourth time, the additive content in the particles is 3.0%, and the peak area ratio A2 of the fourth film sample is calculated; when step S701 to step S704 is performed for the fifth time, the additive content in the particles is 4.0%, and the peak area ratio A2 of the fourth film sample is calculated.
[0069] The number of steps S701 to S704 repeated is n times, and in the above step S7, a total of n+1 peak area ratios A2 are obtained.
[0070] In the above step S706, a standard curve is prepared based on the obtained peak area ratio data of particles with different additive contents to obtain the slope K of the curve.
[0071] In the above step S8, a standard curve is established based on the ratio of the area of the detected characteristic peak of the auxiliary agent to the area of the characteristic peak of the particle, and the slope K of the curve is obtained by the added auxiliary agent content. The grafting rate Y of the grafted material is calculated according to the formula Y=A×K+B, wherein K is the slope of the curve, B is the intercept of the curve, A is the peak area ratio, and A=A1.
[0072] Example
[0073] In this embodiment, Figure 2 This is the detection of POE grafted material of silane KH171, the additive peak is at 1100cm -1 The infrared peak of POE particles is around 718cm -1 About 1100cm -1 The peak areas S1 and 718 cm -1 Substituting the peak area S2 ratio A1 (A1=S1 / S2) into the formula Y=A·K+B can give the grafting rate of silane KH171.
[0074] The present invention is described above by way of example in conjunction with the accompanying drawings. Obviously, the specific implementation of the present invention is not limited to the above-mentioned methods. As long as various non-substantial improvements are made using the method concept and technical solution of the present invention; or the above concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A method for detecting the grafting rate of a grafted material for photovoltaic film, characterized in that: Includes steps: S1, after the grafted material is mixed evenly, sampling is performed; S2, refining the grafted material into a film material on an open mill; S3, taking a film material of a set size as a first film sample, and making the first film sample into a second film sample with a flat surface; S4, placing the second film sample in the solution for soaking; S5, drying the second film sample; S6, testing the infrared spectrum of the second film sample, and calculating the peak area ratio of the second film sample; S7, preparing a standard curve of the relationship between the additive content in the particles and the infrared peak area ratio; S8. Calculate the grafting rate of the grafted material.
2. The method for detecting the grafting rate of the grafted material for photovoltaic adhesive film according to claim 1, characterized in that: In the step S2, the thickness of the film material is 0.09-0.11 mm.
3. The method for detecting the grafting rate of the grafted material for photovoltaic film according to claim 1, characterized in that: In the step S3, the first film sample is melted into the second film sample by a laminating device.
4. The method for detecting the grafting rate of the grafted material for photovoltaic adhesive film according to claim 3, characterized in that: In the step S3, the temperature when laminating the first film sample is 65-75°C.
5. The method for detecting the grafting rate of the grafting material for photovoltaic adhesive film according to any one of claims 1 to 4, characterized in that: In step S4, the solution is ethanol.
6. The method for detecting the grafting rate of the grafted material for photovoltaic adhesive film according to any one of claims 1 to 4, characterized in that: In the step S4, the second film sample is placed in the solution for immersion for at least 3 hours.
7. The method for detecting the grafting rate of the grafting material for photovoltaic adhesive film according to any one of claims 1 to 4, characterized in that: In the step S4, the second film sample is placed in the solution for soaking at least once.
8. The method for detecting the grafting rate of the grafted material for photovoltaic adhesive film according to any one of claims 1 to 7, characterized in that: In the step S5, the temperature for drying the second film sample is 35-45° C., and the drying time is at least 2 hours.
9. The method for detecting the grafting rate of the grafting material for photovoltaic adhesive film according to any one of claims 1 to 8, characterized in that: In the step S6, the peak area ratio A1 of the second film sample is calculated according to the obtained target characteristic peak absorbance peak area S1 and the characteristic peak absorbance peak area S2 of the particle itself, where A1=S1 / S2.
10. The method for detecting the grafting rate of the grafting material for photovoltaic adhesive film according to any one of claims 1 to 9, characterized in that: The step S7 comprises: S701, sampling particles that have not been grafted and contain additive components; S702, refining the particles into a film material on a refining mill; S703, taking a film material of a set size as a third film sample, and manufacturing the third film sample into a fourth film sample with a smooth surface; S704, testing the infrared spectrum of the fourth film sample, and calculating the peak area ratio of the fourth film sample; S705, repeating steps S701 to S704 to obtain peak area ratio data of particles with different additive contents; S706. Prepare a standard curve.